2022
DOI: 10.1002/cpz1.453
|View full text |Cite
|
Sign up to set email alerts
|

Immunofluorescence‐Mediated Detection of Respiratory Virus Infections in Human Airway Epithelial Cultures

Abstract: A diverse collection of viral pathogens target airway epithelial cells for infection, with effects ranging from mild upper respiratory tract symptoms to death of the infected individual. Among these pathogens are recently discovered and/or emergent viruses that sometimes fail to infect commonly used, immortalized cell lines and for which infection phenotypes in the respiratory tract remain unknown. Human airway epithelial cultures have been developed over the past several decades and have proven to be a useful… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…RSV and human parain uenza virus may display comet shaped foci early in infection, but for these viruses the foci merge and grow to occupy the majority of the culture surface area, rather than remaining distinct as in SARS-CoV-2 in the current study 5,30 . For in uenza A virus, while comet shaped foci have been anecdotally reported (personal communication), it appears to be a relatively uncommon phenomenon and no published images were identi ed 33,34 . Comparisons between viruses based on published literature are suspect owing to differences in infection, culture conditions, and imaging protocols.…”
Section: Discussionmentioning
confidence: 99%
“…RSV and human parain uenza virus may display comet shaped foci early in infection, but for these viruses the foci merge and grow to occupy the majority of the culture surface area, rather than remaining distinct as in SARS-CoV-2 in the current study 5,30 . For in uenza A virus, while comet shaped foci have been anecdotally reported (personal communication), it appears to be a relatively uncommon phenomenon and no published images were identi ed 33,34 . Comparisons between viruses based on published literature are suspect owing to differences in infection, culture conditions, and imaging protocols.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that measurement of calcitonin using antibody-conjugated fluorospheres can differentiate atypical bacterial meningitis from viral encephalitis in children ( 49 ). Immunofluorescence microscopy enables single-cell analysis of samples and preserves spatial information within cells as well as throughout the culture, and can be paired with image analysis tools to localize to the virus or detect expression of associated viruses at the single-cell level, but this technique is only useful in the absence of infected cells ( 50 ).…”
Section: Etiological Examinationmentioning
confidence: 99%